TRAINING ON EDU-AGROTOURISM FINANCIAL GOVERNANCE OF KWT BINA PERTANI, KAMPUNG LIMAN BENAWI, TRIMURJO, CENTRAL LAMPUNG - Sri Retnaning Rahayu; Elly Lestari Rustiati; Dian Neli Pratiwi; Ana Septiana; Muhammadi Ridho Al Amin; Angga Kurniawan (Ann Publisher, 2024)
A training session on Edu-agrotourism financial governance was conducted for KWT Bina Pertani, a farmer women's group in Kampung Liman Benawi, Trimurjo, Central Lampung, on January 26, 2024. The primary objective of this fundamental accounting and finance training was to enhance the understanding of financial management and the skills of KWT Bina Pertani members and village civil servants. The curriculum encompassed an overview of financial statements, rudimentary bookkeeping, the compilation of financial statements, and strategies for crop pricing. The training objectives were achieved through coordination, agreement, training materials and equipment preparation, and activities and evaluations. The training was delivered face-to-face with direct practice, and the participants enthusiastically received it. The training session yielded positive outcomes, with successful material delivery and achievement of the activity objectives.